Model Pengabdian Masyarakat Berbasis Kawasan - Fakhruddin, Fakhruddin (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
Research problems increase community empowerment through the process of human capital and physical capital in the area around the community. The research objective is to develop a model that is supported by the concept of theoretical development. This research focuses on "process" as a key success for improving people's welfare. The relationship between capital and empowerment improvement will be tested in this study by putting the empowerment process as a mediating variable to explain activities related activities. The data used are primary and secondary data. Primary data is collected using survey method techniques through questionnaires. Furthermore, it is described and analyzed using theory. The findings of the study show that the service model leads to an increase in community empowerment, where (1) the model consists of two stages of empowerment, and (2) a model which indicates that three stages of the activity process are needed. There is a correlation where the higher the empowerment process will be able to create community empowerment. Implementation of this model states that empowerment wants the development of human capital and physical capital, and it will be even better if empowerment is supported by the development of the capacity of the actors of empowerment.